Keragaman Kupu-kupu Pemakan Buah Busuk di Perbatasan Zona Rehabilitasi Taman Nasional Gunung Ciremai Kecamatan Cigugur, Kuningan - Trisno Haryanto; Imam Widhiono; Bambang Heru Budianto (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Butterflies can be classified based on their feed sources into a nectar-feeding and frugivorous butterfly. Frugiforus butterflies are very sensitive to environmental changes. Furthermore, they are easy to be observed by using a simple sampling method. The research on the diversity of frugivorous butterflies was carried out in the rehabilitation zone of the Ciremai Mountain National Park (TNGC) Region Cigugur, Kuningan. The purpose of this study was to obtain information about the diversity of frugivorous butterflies in the rehabilitation zone of TNGC Region Cigugur, Kuningan, as an indicator of land fragmentation and improve the management of TNGC in the use of natural resources, especially for research activities. Butterflies were sampled using a survey method with purposive sampling using bait traps with rotten bananas as bait. Research locations were in the frontier of the rehabilitation area, Cigugur, Kuningan, West Java, perpendicular to the forest frontier along 200 m, which is at a distance of 0-50 m, 50-100 m, 100-150 m, and 150-200 m. The results showed that the diversity of frugivorous butterfly was relatively high with the discovery of 11 types of butterflies from 1 family Nymphalidae.